New Molecular Data on Squat Lobster from the Coast of Sao Paulo State (Brazil) (Anomura: Munida and Agononida) and Insights on the Systematics of the Family Munididae - Miranda, I. [UNESP]; Peres, P. A.; Tavares, M. D.S.; Mantelatto, F. L. (Springer Nature, 2021)
The squat lobsters Munida Leach, 1820 and Agononida Leach, 1820 are part of the most speciose genera in the diverse family Munididae. Despite the considerable diversity (>240 species), the Brazilian waters encompass 18 species so far (17 Munida and 1 Agononida), only 7 (6 and 1, respectively) of which recorded from the coast of Sao Paulo. The decapod fauna along the coast of Sao Paulo has been studied in the recent past, mostly using classical alpha morphology. In the present study, we carried out a molecular analysis to phylogenetically contextualize the species of Munida and Agononida and address future directions on the systematics of the group. The current investigation results from a long-term multidisciplinary taxonomic project that combined analyses of adult specimens for accurate and detailed identification of the biodiversity of marine decapod crustaceans from Sao Paulo state. Sampling was carried out in five major regions along the Sao Paulo coast from 2011 to 2018: Ubatuba, Caraguatatuba, Sao Sebastiao and Ilhabela, Santos and Sao Vicente, and Cananeia and Ilha Comprida. Additional material from the MZUSP collections was used to complete the analysis when fresh material was not obtained during the surveys. Previous to molecular analysis, the material was identified by classical literature. We obtained six species out of seven recorded, with sequences of cytochrome oxidase subunit I-barcode region and 16S generated from six species. We include additional genera and close species to run the analysis to better contextualize the phylogenetic positioning of the target species. Our tree shows a clear recognition of some of Sao Paulo species and points out systematics inconsistencies in Munididae. Based on the present results, and pending future more complete analyses, Munididae should be revised.
Keywords: 16S rRNA; Cytochrome oxidase subunit I; DNA markers; Molecular phylogeny; Western Atlantic